Analisis Faktor yang Berhubungan dengan Kinerja Perawat di Instalasi Rawat Inap Rsud Ratu Zalecha Martapura - Aqiella Farida Salsabila; Rosihan Adhani; Iwan Aflanie; Syamsul Arifin; Nia Kania (Jurnal Sains dan Kesehatan, 2026)
Nursing care in hospitals is still below the established standard of 80%, thus reflecting suboptimal nurse performance. This condition is thought to be influenced by factors such as rewards, workload, length of service and supervision. This study aims to analyze the relationship between rewards, workload, length of service, and supervision with nurse performance in the Inpatient Unit of Ratu Zalecha Martapura Regional Hospital. This study used a quantitative method with an observational analytical design using a cross-sectional approach. The study sample consisted of 152 nurses selected using cluster proportional random sampling technique. Data were collected using a questionnaire and analyzed using the chi-square test and multiple logistic regression. The results showed a significant relationship between rewards and nurse performance (p-value=<0.001), workload and nurse performance (p<0.001), and supervision and nurse performance (p-value=<0.001). Length of service did not show a significant relationship with nurse performance (p-value=0,968). Multivariate analysis showed that supervision was the most dominant factor related to nurse performance. Thus, compensation, workload, and supervision are related to nurse performance, while length of service is not related to nurse performance in the Inpatient Unit of Ratu Zalecha Regional Hospital, Martapura. The hospital is expected to improve supervision, workload management, and training and recognition for nurses to improve the quality of nursing services.